Evaluation of the total fluoride intake of 4-7-year-old children from diet and dentifrice (Journal of Applied Oral Science, 2003)
This study measured the total daily fluoride (F) intake of 21 children, living in Bauru, a fluoridated community. F intake from diet (D) and dentifrice (B) was determined for 2 groups of children: A (4-5-year-old) and B (6-7-year-old). The method of 24-hour duplicate diet was used. F ingested from dentifrice was indirectly obtained, subtracting the amount expelled and the amount left on the toothbrush from the amount initially loaded onto the brush. F analysis was carried out with the ion specific electrode (Orion 9409), after hexamethyldisiloxane-facilitated diffusion. The amount of F intake from D and B was divided by the child weight and total intake (T) was calculated by adding D and B. Data were analyzed by Students "t" (p